Urinary Bladder Matrix Improves Irradiated Wound Healing in a Murine Model. Issue 5 (May 2022) - Yao, Jingxin; Vangsness, Kella L.; Khim, Phillip; Raghuram, Anjali C.; Park, Sun Young; Yu, Roy; Wang, Jin; Jiao, Wan; Wong, Alex K.
Abstract: Radiation skin damage is associated with chronic wounds and poor healing. Existing localized treatment modalities have limited benefit. Therefore, there has been increased interest in biologically based solutions. In this study, we aimed to determine the effect of topical urinary bladder matrix (UBM) on chronic irradiated skin wounds using an established murine model. Our findings demonstrated that topical urinary bladder matrix significantly accelerated the healing of irradiated wounds on day 7 ( P = 0.0216), day 14 ( P = 0.0140), and day 21 ( P = 0.0393). Histologically, urinary bladder matrix treatment was associated with higher-quality reorganization and reepithelialization of wounds, an increased density of myofibroblasts ( P = 0.0004), and increased collagen deposition ( P < 0.0001). In addition, quantitative real-time polymerase chain reaction data demonstrated decreased expression of profibrotic mediators ( P = 0.0049). We conclude that urinary bladder matrix may be a useful, noninvasive, adjunctive therapy for the treatment of chronic irradiated skin wounds.